Strategi Guru dalam Mengembangkan Sikap Keterampilan Sosial Siswa pada SMP Negeri 2 Seram Barat - Agustinus Nindatu; Jurgen R. Litualy; Yosepus A. Hallatu (Jurnal Pendidikan dan Kewarganegara Indonesia, 2024)
Lack of social skills in students has an impact on students' indifferent attitude towards tasks given by teachers, lack of student participation in school activities and lack of interaction between students so that there are students who tend to be closed and have no sense of concern for their friends. Therefore, the role of teachers is needed in providing a positive contribution to the development of students' social attitudes. This type of research is descriptive qualitative and the data collection techniques used are observation and interviews. Furthermore, the data obtained were analyzed descriptively qualitatively which aims to describe the problems that occur and relate them to the specified variables and can also be discussed in narrative form. The results of the study found that social skills as an interaction ability between teachers and teachers and teachers with students, and students with students so social skills in schools are related to the relationship of school community interactions, the role of teachers in developing students' social skills attitudes is shown through a learning approach in the classroom, for example through character values ​​explained in learning with the aim of training students to have a sense of sympathy, concern, tolerance which are part of social skills so that in the development of students' social skills at SMP Negeri 2 Seram Barat, students can accept the application of social skills attitudes well, this can be seen from student interactions both with teachers and with peers. Application of Social Skills attitudes in Learning for students in class that in the learning process carried out by teachers in class at SMP Negeri 2 Seram Barat, using learning methods such as: question and answer methods, lecture methods, demonstration methods, discussion methods, jigsaw learning methods, peer teaching methods. The application of social skills attitudes in classroom learning, the right method is a method that trains student cooperation, trains how to convey opinions such as question and answer methods, discussion methods. In implementing social skills attitudes, not only teachers have an important role, but social skills are also carried out by other teachers in classroom learning using learning methods that can develop students' social skills.